Mean platelet volume predicts survival in pancreatic cancer patients with synchronous liver metastases - Yin, Ji-bin; Wang, Xin; Zhang, Xin; Liu, Li; Wang, Rui-tao (Scientific reports, 2018)
Most pancreatic cancer (PC) patients manifest multiple liver metastases at the time of diagnosis. Activated platelets play a key role in tumor growth and tumor metastases. Mean platelet volume (MPV) is a platelet index and is altered in patients with malignancies. This study aimed to evaluate whether MPV can effectively predict death in PC patients with synchronous liver metastases. The clinical data of 411 PC patients with synchronous liver metastases between January 1, 2006 and December 31, 2013 were retrospectively analyzed. Subjects were divided into two groups by MPV levels. Clinicopathological data were collected retrospectively and relationships between MPV levels and clinical parameters were evaluated. Survival analysis was performed. Increased MPV was not significantly correlated with tumor location, tumor size, and CA19.9. The Kaplan-Meier analysis showed that the overall survival of patients with MPV > 8.7 fL was significantly shorter than that of those with MPV ≤ 8.7 fL (log-rank p < 0.001). Multivariable Cox proportional hazards model identified MPV as an independent poor prognostic factor for overall survival. In conclusion, elevated MPV is associated with worse survival outcome in PC patients with synchronous liver metastases. Further studies are warranted.